Accurate, sensitive, and precise determination of cobalt in soil matrices by the combination of batch type gas-liquid separator-assisted photochemical vapor generation and atomic absorption spectrophotometry - Buyukpinar, Cagdas; San, Nevim; Komesli, Okan Tarik; Bakirdere, Sezgin (SPRINGER, 2019)
Determination of cobalt at low concentrations is an important issue because of its potential harmful effects on human health. Although flame atomic absorbance spectrometry (FAAS) is a fast and cheap method, it has high detection limits compared to other methods due to low nebulizer efficiency. In this study, the sensitivity, accuracy, and precision of the conventional FAAS were tried to be improved for cobalt determination using a photochemical vapor generation (PVG) system equipped with a batch type gas-liquid separator (BTGLS). The system parameters including organic acid type and concentration, UV irradiation period, mixing type, atomizer temperature, carrier gas flow rate, and sample volume were optimized to improve the detection power. The limits of detection and quantification were found to be 8.7 and 28.9gL(-1), respectively. The low relative standard deviation results indicated high precision. Applicability and accuracy of the method to soil samples was determined by recovery studies and percent recoveries were obtained between 98.9-107.0%.
Keywords: Cobalt; Photochemical vapor generation; Volatile species; Atomic absorption; SAMPLES; WATER; NICKEL; SPECTROMETRY; ANTIMONY; SELENIUM; CADMIUM; URINE; LEAD; Environmental Sciences & Ecology